(untitled) (Muitas Vozes, 2021)
Haegeman (2012) observes that, in central conditional sentences in English, there can be no argument topicalization. In her analysis, the author proposes that the argument fronting to the periphery of the sentence is the factor responsible for blocking the raising of the conditional operator from TP to CP. In Portuguese, unlike English, it is possible the fronting of arguments. In order to account for this difference, we propose that, in Portuguese, when there is argument fronting in conditional sentences, the fronted constituent is a phrase directly merged in the left periphery. Our proposal is that such elements are coreferential of a visible or null pronoun, considering that Portuguese is a language which allows null objects (CYRINO, 1994). Under this approach, fronting structures in conditional sentences in Brazilian Portuguese are, therefore, clauses manifesting Clitic Left Dislocation (CLLD), since there was no movement of the fronted constituent. Thus, the absence of syntactic raising of topicalized phrase makes it possible the movement of the conditional operator to the CP system.